Extension of the Stöber Method to Construct Mesoporous SiO2 and TiO2 Shells for Uniform Multifunctional Core–Shell Structures. (15th October 2012) - Li, Wei; Zhao, Dongyuan
Abstract Core–shell nanoparticles (CSNs) have attracted considerable attention because of their promising applications in a wide range of fields. Recently, substantial efforts have been focused on the development of facile and versatile methods for preparing CSNs with mesoporous SiO2 or TiO2 shells because of their fascinating properties, such as high surface area, large pore channels and high pore volume. This Research News reviews the recent progress in facile, versatile and reproducible approaches which are simply extended from the well‐known Stöber method to construct mesoporous SiO2 and TiO2 shells for uniform multifunctional core–shell nanostructures. Several strategies, including the surfactant‐templating process, the long‐chain organosilane‐assisted approach, the phase transfer assisted surfactant‐templating process, and the kinetics‐controlled coating approach, are discussed. In addition, new trends in this field for the creation of multifunctional CSNs and novel nanostructures are highlighted.